African Philosophy in Brazil: Orality, Agraphia, Ancestry and the Timbuktu Manuscripts - Tchivole, Tarcísio Afonso (Sententiae, 2025)
This article analyzes the reception of African philosophy in Brazilian postgraduate studies over the last two decades. The Timbuktu Manuscripts stand out as an epistemic turning point, as they highlight autonomous forms of African philosophical thought with repercussions in the Brazilian context. The persistence of the agraphia myth demands a decolonized approach that integrates oralities, textualities and written ancestries as legitimate and plural expressions of African philosophical knowledge. The results of the analysis point to the urgency of a critique of the categories of agraphia, orality and ancestry, as traditionally conceived, and to the importance of rediscovering and appreciating the Timbuktu Manuscripts.